Campaign Strategy of The Prosperous Justice Party in Banda Aceh City For The 2024 General Election - Fathinah, Aufa; Nugraha, Fajar (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2025)
The main issue underlying this research is how PKS can design a campaign strategy that can survive amidst changing political communication patterns, limited resources, and the declining effectiveness of conventional campaigns that have been the party's strengths. This research is important and interesting because the PKS campaign in Banda Aceh for the 2024 General Election demonstrated a unique phenomenon: the use of a hybrid strategy that combines a door-to-door approach based on cadre proximity with creative campaign techniques such as flash mobs and massive digital messaging. This study aims to analyze the planning, implementation, and evaluation of the Prosperous Justice Party (PKS) campaign strategy in Banda Aceh City for the 2024 General Election. The method used is descriptive qualitative with data collection through direct interviews with the PKS campaign winning team in Banda Aceh City. The results show that PKS implemented effective communication strategies, such as door-to-door campaigns, indirect mass campaigns, and creative flash mob techniques to reach voters and increase public participation. This combination of traditional and digital strategies has produced significant impacts: increased emotional closeness with voters, increased public exposure to campaign activities, and an increase in PKS's vote share of 17.14% compared to the 2019 Election. This means that PKS's campaign strategy has not only succeeded in maintaining political support, but also expanding the voter base through innovative political communication. This research contributes to the understanding of political campaign strategies in the regional context and provides practical insights for political parties in increasing campaign effectiveness. Persoalan utama yang melatarbelakangi penelitian ini adalah bagaimana PKS merancang strategi kampanye yang mampu bertahan di tengah perubahan pola komunikasi politik, terbatasnya sumber daya, serta menurunnya efektivitas kampanye konvensional yang selama ini menjadi kekuatan partai. Penelitian ini menjadi penting dan menarik karena kampanye PKS di Banda Aceh pada Pemilu 2024 memperlihatkan fenomena unik: penggunaan strategi hibrida yang menggabungkan pendekatan door-to-door berbasis kedekatan kader dengan teknik kampanye kreatif seperti flash mob dan penyebaran pesan digital yang masif. Penelitian ini bertujuan untuk menganalisis perencanaan, pelaksanaan, dan evaluasi strategi kampanye Partai Keadilan Sejahtera (PKS) di Kota Banda Aceh pada Pemilihan Umum Tahun 2024. Metode yang digunakan adalah kualitatif deskriptif dengan pengumpulan data melalui wawancara langsung dengan tim pemenangan kampanye PKS Kota Banda Aceh. Hasil penelitian menunjukkan bahwa PKS menerapkan strategi komunikasi yang efektif, seperti kampanye rumah ke rumah, kampanye massa tidak langsung, dan teknik kreatif flashmob untuk menjangkau pemilih dan meningkatkan partisipasi masyarakat. Kombinasi strategi tradisional dan digital ini menghasilkan dampak signifikan: meningkatnkan kedekatan emosional dengan pemilih, meningkatnya eksposur publik terhadap aktivitas kampanye, serta bertambahnya perolehan suara PKS sebesar 17,14% dibandingkan Pemilu 2019. Artinya strategi kampanye PKS tidak hanya berhasil mempertahankan dukungan politik, tetapi juga memperluas basis pemilih melalui inovasi komunikasi politik Penelitian ini memberikan kontribusi dalam pemahaman strategi kampanye politik pada konteks regional serta memberikan wawasan praktis bagi partai politik dalam meningkatkan efektivitas kampanye.